The deadweight loss of christmas - Reply - Laura Birg; Simon Pommeranz (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2018)
In this paper, we study the welfare effects of Christmas presents with a focus on the effect of presents for gift-givers. Based on a survey among students at the University of Göttingen, Germany, we find that the vast majority of gift-givers prefers in-kind gifts compared to gifts of money. The average present in our survey has a price of 36 Euro and results in a "giver's surplus" of 10 Euro. This indicates a welfare gain of approximately 143% from the average giver's perspective. The welfare gain for presents to friends and partners is lower than for presents to close family members. Our empirical analysis shows a negative effect of a present's price on the welfare gain for gift-givers.
Keywords: D61; D64; H42; Z1; 330; presents; gift-giving; Christmas; welfare